Effects of tillage practices on some key soil parameters : A case study in the Kwazulu-Natal Midlands, South Africa - Esmeraldo, Michael Quinten (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.